An illustrated key to Neotropical species of the genus Meteorus Haliday (Hymenoptera, Braconidae, Euphorinae) - Helmuth Aguirre; Luis Felipe Ventura de Almeida; Scott Richard Shaw; Carlos Eduardo Sarmiento Monroy (ZooKeys, 2015)
A comprehensive key for 75 species of Meteorus distributed across 15 Neotropical countries is presented. Eleven new species from Bolivia, Costa Rica and Ecuador are described: M. albistigma, M. carolae, M. eurysaccavorus, M. fallacavus, M. flavistigma, M. haimowitzi, M. magnoculus, M. martinezi, M. microcavus, M. noctuivorus and M. orion. Expanded range distributions are recorded for M. andreae, M. farallonensis, M. guineverae, M. jerodi, M. kraussi, M. papiliovorus and M. quimbayensis. The host of M. jerodi is reported for the first time: a noctuid larva feeding on Asteraceae. Meteorus papiliovorus is recorded attacking Papilionidae larvae in Ecuador, therefore displaying a similar host family preference as formerly documented from Costa Rica and Colombia.